Stoicism and the Tragedy of the Commons - Gregory Ponthiere (Global Labor Organization (GLO), 2024)
This paper revisits the Tragedy of the Commons - a Pareto-dominated overuse of a common resource - through the lenses of Stoicism, and, in particular, of the Stoic discipline of desires, according to which one should wish for nothing that is not under one's control. When the Stoic discipline of desires is modelled as a requirement of indifference between outcomes differing only on things out of control, Stoic agents are shown not to overuse the common resource. Alternatively, when the Stoic discipline of desires requires indifference between best outcomes under each circum- stance, the Nash equilibrium, if it exists, cannot be Pareto-dominated. Depending on how the Stoic discipline of desires is formalized, a recen- tering of agents towards things under their control either allows them to avoid overusing the commons, or makes the use of commons not "tragic".
Keywords: Q24; D62; D91; Z1; 330; Tragedy of the Commons; Stoicism; rationality; common resource game; land overuse